Utilization of Waste Polymer (Rubber, Plastic) To Enhance the Strength of Asphalt Aggregate in Flexible Pavement (International Journal of Innovative Research in Engineering & Management, 2022)
Globally, sustainability is indeed an  urgent necessity in the construction sector, and the use of  waste products in road building is becoming more common  recommended in order to lessen the environmental effect.  A great variety of novel materials and techniques have  been developed in the highway infrastructure to establish  their feasibility for pavement design, construction, and  maintenance. Plastics and rubbers being two examples.  The amount of plastic garbage in landfill is growing as the  population grows and lifestyles change. Similarly, most  tire’s, particularly those used in automobiles, are made of  synthetic rubber. The management of either is a severe  issue. At the same time, the growing number of cars  stresses the need for roads of higher quality and  engineering design. This plastic & rubber can be utilized  to partially replace conventional materials in order to  improve desirable mechanical properties for a certain road  mix. In this study a comparison is made between polythene and  crumb rubber used to modify bituminous mixes. The  percentage of bitumen is varied from 3,3.25,3.5,3.75,4 and 4.25 percent and the quantity of polythene and crumb  rubber is varied in the percentages of 7.5,10,12.5 and 15  percent. The marshall stability procedure was used to  prepare the specimens and stability values flow value, air  void and VMA was found for the specimens. The optimum  value of marshall stability was obtained at 4.25% bitumen  content and 10% polythene or crumb rubber  percentages.The value of Marshall stability was more for  polythene modified bituminous mix. However, the flow  values were grater for crumb bituminous mix. From the  results it was concluded that polythene is a better modifier  compared with crumb rubber.
Keywords: Waste Polymer; Asphalt; Flexible Pavement; Rubber; Plastic